(untitled) (Agroindustria, Sociedad y Ambiente, 2024)
The potato constitutes the third most consumed food after corn and wheat, the study of the patterns of dry matter allocation to the different parts of the plant is important for the evaluation of the growth rate, productivity and level potato yield. Due to the above, it is important to continue exploring the processes that determine the growth of the potato, so in this research the accumulation and distribution of dry matter in the different organs of the Mukasinia variety potato plant from the state of Trujillo one was evaluated. of the largest potato producers in the Venezuelan Andes. The experiment was installed on a plot of the La Cristalina Experimental Field of the INIA-Trujillo, located at 2,630 meters above sea level, with an average temperature of 14 °C, annual precipitation of 890 mm and RH of 87%; Prior to planting, a soil analysis was carried out in order to know the state of the fertility of the plot. An experimental design of randomized complete blocks was used, with 4 repetitions and an experimental unit consisting of 20 plants each. The distribution of dry matter in the Mukasinia variety, in the different organs of the plant allowed us to find relevant differences in terms of the behavior of dry matter accumulation in roots, leaves, stems and tubers, being the average percentages of the different organs of the plant at the end of the root crop cycle 12%; sheet 30%; stem 20% and tubers 39% respectively.